A social and democratic Europe? Obstacles and perspectives for action - Daniel Seikel (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2016)
Everywhere in Europe, support for the European integration process decreases. More and more Europeans associate the European Union with the dismantling of social and democratic rights. Fundamental social rights clash with the market-liberal single market law, the key institutions of the European social model are undermined. What are the causes for this development? Which changes are necessary to achieve a more social and democratic Europe? This article reconsiders the concept of Social Democracy and suggests using it as a blueprint for a fundamental change of course of the European integration process. Starting point is the finding that the institutional architecture of the European multi-level system creates a systematic imbalance between liberalization and social regulation. On the basis of this problem analysis, I identify three policy fields that are of central importance for creating a social and democratic Europe: an "open" constitution for Europe, social minimum standards and the recuperation of the fiscal capacities of the political system.
Keywords: 330